Paulo Freire's philosophy of education : origins, developments, impacts and legacies - Irwin, Jones (New York : Continuum, 2012)
"A critique of Freire's thinking, the influence of his work and ways in which his theories may be developed into the future"--
Includes bibliographical references and index.
Keywords: Freire, Paulo, -- 1921-1997 -- Criticism and interpretation; Education -- Philosophy; Critical pedagogy; EDUCATION / Computers & Technology; EDUCATION / Teaching Methods & Materials / General